Pengembangan Media Pembelajaran Interaktif Berbasis Android untuk Meningkatkan Keterampilan Lompat Jauh Gaya Jongkok Siswa SMA Negeri 3 Makassar - Suriah Hanafi (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
Purpose of the study: This research aims to develop and test the effectiveness of interactive Android-based learning media for long jump material using the squat style at SMA Negeri 3 Makassar. Materials and methods: The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 36 students of class X MIPA selected through purposive sampling technique. Data collection techniques included expert validation sheets (media and material experts), student practicality questionnaires, and long jump skill tests. Data were analyzed using descriptive statistics and N-gain test. Results: The results showed that: (1) the validation of media experts obtained a score of 4.42 with a